Penerapan Metode SOSTAC dalam Perancangan Sistem Informasi untuk Meningkatkan Strategi Pemasaran - Tristianto, Wahyu; Yasin, Ikbal (Journal of Information System Research (JOSH), 2024)
CV Wahyu Putra is one of the companies engaged in agriculture that has not utilized the productivity of information technology in its operational activities, the lack of business development of the company in developing a digital marketing strategy, currently the dissemination of information about products is limited to word of mouth, this study seeks to provide new opportunities by developing a marketing information system for CV Wahyu Putra through a website and social media marketing accounts. Where from this study, namely designing an information system to improve marketing strategies by utilizing the results of direct interviews with five informants, including representatives of business development, market players, and the general public, these findings are used as reference materials for formulating analysis with the SOSTAC method which consists of 6 stages, namely Situation Analysis, Objective, Strategy, Tactic, Action and Control. Where this study produces the design of an information system to improve marketing strategies on a marketing website and Instagram social media account which functions as a marketing media and sales information system that is tailored to user needs.